2010
DOI: 10.1051/vetres/2010009
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell kinetics in the ovine abomasal mucosa following hyperimmunization and challenge withHaemonchus contortus

Abstract: Sheep were sensitized by repeated infection with Haemonchus contortus L3, followed by a 12 week rest period, and an abomasal cannula was surgically implanted in all sheep. Seven of the sensitized sheep were subsequently challenged with 50 000 H. contortus L3 while 4 control sheep were challenged with saline. Biopsy samples were taken using a fibreoptic endoscope on days 0, 1, 2, 3, 5, 7 and 28 after challenge and leukocyte subpopulations quantified by (immuno)histology. Differential blood cell counts were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 22 publications
1
24
2
Order By: Relevance
“…A significant positive correlation between ␥␦ T cells and eosinophil numbers at the abomasal mucosa has been reported in early infection and associated with resistance against the larval stages (Robinson et al, 2010). In this response, ␥␦ T cells were postulated to recruit tissue eosinophils through local IL-5 cytokine production, followed by antibody-mediated eosinophil killing of tissue larvae.…”
Section: Discussionmentioning
confidence: 98%
“…A significant positive correlation between ␥␦ T cells and eosinophil numbers at the abomasal mucosa has been reported in early infection and associated with resistance against the larval stages (Robinson et al, 2010). In this response, ␥␦ T cells were postulated to recruit tissue eosinophils through local IL-5 cytokine production, followed by antibody-mediated eosinophil killing of tissue larvae.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies in immunized sheep showed that globule leukocytes were implicated in the immune exclusion of challenge larvae [2729]. Recently, Robinson et al (2010) monitored the local cellular immune response in immunized sheep challenged with H. contortus and observed a peak of globule leukocyte infiltration in the abomasal mucosa at five days after infection [30]. In accordance with this study, our data suggest that globule leukocytes would be implicated in the response against larval stage of H. contortus a mechanism associated with the genetic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This has been proved for T. circumcincta (Li et al, 2012;Shaw et al, 2012). While the association between serum IgA and infection ΑΡΣΕΝΟΠΟΥΛΟΣ Κ., ΣΥΜΕΩΝΙΔΟΥ Η., ΠΑΠΑΔΟΠΟΥΛΟΣ Η. mice and Robinson et al (2010) against H. contortus in sheep. Researchers have observed a rapid eosinophil recruitment around L4 larvae resulting to a considerable damage to H. contortus larval surface, especially in gastric pits of immunized sheep (Balic et al, 2006).…”
Section: The Role Of Immunoglobulin a (Iga) And Immunoglobulin E (Ige)mentioning
confidence: 83%